2015
DOI: 10.1038/mt.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptors With Mutated IgG4 Fc Spacer Avoid Fc Receptor Binding and Improve T Cell Persistence and Antitumor Efficacy

Abstract: The success of adoptive therapy using chimeric antigen receptor (CAR)-expressing T cells partly depends on optimal CAR design. CARs frequently incorporate a spacer/linker region based on the constant region of either IgG1 or IgG4 to connect extracellular ligand-binding with intracellular signaling domains. Here, we evaluated the potential for the IgG4-Fc linker to result in off-target interactions with Fc gamma receptors (FcγRs). As proof-of-principle, we focused on a CD19-specific scFv-IgG4-CD28-zeta CAR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(198 citation statements)
references
References 50 publications
(77 reference statements)
4
179
1
Order By: Relevance
“…Consistently, when the purified CD8 C T CM and CD8 C T N/SCM cells were transduced with lentivirus encoding CD19R (EQ) to ensure enhanced potency after adoptive transfer, 31,32 T CM -CD19R displayed higher fold expansion in vitro (30 vs.8 folds for total cells and 47 vs.12 folds for CAR C T cells) (Fig. S6A, B) and superior antitumor activity to T N/SCM -CD19R (Fig.…”
Section: Cd19car Ctls Derived From Cd8mentioning
confidence: 70%
“…Consistently, when the purified CD8 C T CM and CD8 C T N/SCM cells were transduced with lentivirus encoding CD19R (EQ) to ensure enhanced potency after adoptive transfer, 31,32 T CM -CD19R displayed higher fold expansion in vitro (30 vs.8 folds for total cells and 47 vs.12 folds for CAR C T cells) (Fig. S6A, B) and superior antitumor activity to T N/SCM -CD19R (Fig.…”
Section: Cd19car Ctls Derived From Cd8mentioning
confidence: 70%
“…These reduced levels of T cells may have benefited the recipients, as they did not suffer adverse events associated with a cytokine storm stemming from synchronous activation of administered CAR T cells encountering large numbers of CD19 + cells (4,8). Modifications to the CAR stalk to reduce binding of Fc receptor(s) may further improve the persistence of the genetically modified T cells (63). A followup clinical trial based on the SB system to address these concerns is enrolling at MD Anderson (IND no.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] For example, using a CD19 tumor model, Hudecek et al showed that interactions between the IgG4-derived spacer of their CD19-CAR T cells and FcgR-expressing murine Ly6CC cells led to their sequestration in the lungs. 9 However, in their study, this problem was easily resolved by simply mutating the FcgR binding site (within the CH2 region) as follows: (i) aa233 was deleted and aa234-236 (FLG) were substituted for PVA; and (ii) N (aa297) was substituted for Q.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the mechanism behind this "non-specific" expansion, we examined whether interactions between the IgG1-CH2CH3 spacer region of our P1.CAR and Fcg receptor-expressing cells could be responsible for this phenomenon. [8][9][10][11] Thus, we cultured NT and P1.CAR T cells at a 1:1 ratio with human monocytes, macrophages and NK cells, all of which express different types of FcgRs (CD64-FcgRI, CD32-FcgRII, and CD16-FcgRIII) at varying intensities (Fig. 1F).…”
Section: Car-psca T Cells Exhibit Potent In Vitro Antitumor Effects Bmentioning
confidence: 99%